Nonalcoholic Fatty Liver Disease in a Sample of Iranian Women with Polycystic Ovary Syndrome - Mehrabian, Ferdous (Int J Prev Med, 2017)
INTRODUCTION: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women in reproductive age that is associated with insulin resistance (IR) and metabolic abnormalities which are also a part of metabolic syndrome (Met S). This study was aimed to determine the prevalence of nonalcoholic fatty liver disease (NAFLD) women diagnosed with PCOS based on the Rotterdam criteria from January 2013 to June 2014. METHODS: In this cross-sectional study, 75 women with PCOS and 75 healthy controls were enrolled. Anthropometric parameters, biochemical and hormonal investigation, were measured in all women. IR was calculated by homeostasis model assessment. Abdominal ultrasonography and biochemical tests were used to determine the NAFLD. RESULTS: The level of triglyceride, cholesterol, low-density lipoprotein, aspartate aminotransferase, alkalin phosphatase, fasting insulin, and homeostatic model assessment index in women with PCOS were significantly higher than women without PCOS. High-density lipoprotein and alanine aminotransferase (ALT) in women with PCOS were significantly lower. The frequency of IR women with or without PCOS was 53.3% and 29.3%, respectively (P = 0.003). The frequency of Met S in women with PCOS was 33.3% and in other was 10.7% (P = 0.001). The prevalence of fatty liver in women with or without PCOS was 38.7% and 18.7%, respectively (0.008). In women with PCOS, body mass index (BMI) (odds ratio [OR] = 4.25; P = 0.046), ALT (OR = 1.62; P = 0.005), fasting insulin (OR = 1.32; P = 0.032), and IR (OR = 58.17; P = 0.025) were associated with a higher fatty liver. CONCLUSIONS: NAFLD is frequent in patients with PCOS with combination with other metabolic derangements. BMI, ALT, fasting insulin, and IR are the risk factors for high prevalence of NAFLD in women with PCOS.